Comparative nephroprotective efficiency of polyfunctional mucous-adhesive phytogels - Gozhenko, A. I.; Levitsky, A. P.; Stepan, V. T.; Selivanskaya, I. A.; Pustovoit, I. P. (Journal of Education, Health and Sport, 2021)
Aim. To compare the nephroprotective effect of oral applications of different phytogels in experimental kidney pathology. Methods. We used phytogels: "Kvertulin" (quercetin + inulin + calcium citrate), "Biotrit" (juice from wheat germ) and "Dubovy" (extract from oak wood). Experimental models were reproduced in rats: diabetic syndrome, prednisolone immunodeficiency, intoxication with thermal peroxide sunflower oil. The condition of the kidneys was assessed by changes in the level of biochemical markers in the kidney tissue (elastase, urease, lysozyme, MDA, the degree of dysbiosis). Results. Experimental pathologies cause an increase in the level of elastase, urease, MDA, the degree of dysbiosis, and a decrease in lysozyme activity in the kidneys. Oral application of phytogels caused a decrease in the activity of elastase, urease, MDA content and the degree of dysbiosis, but increased the activity of lysozyme. When recalculating the degree of decrease in elastase activity and increase in lysozyme activity per 1 g of phytogel or 1 mg of active principle (quercetin or the amounts of polyphenols), phytogel "Kvertulin" turned out to be the most effective anti-elastase agent, and phytogel "Biotrit" turned out to be the most effective lysozyme-reducing agent. Conclusion. Oral applications of multifunctional mucous-adhesive gels have a nephroprotective effect in experimental kidney pathology.